1997
DOI: 10.1046/j.1365-2095.1997.00096.x
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability and interactions with other micronutrients of three dietary iron sources in Atlantic salmon, Salmo salar , smolts

Abstract: Atlantic salmon, Salmo salar L., with mean initial weight of 60 g were fed a diet based on cod muscle meal supplemented with elemental iron, iron sulphate or haem-bound iron in concentrations of 0, 25, 50, 100, 500 and 1500 mg iron kg -1 for 8 weeks.No significant differences in growth or mortality were found, except in fish fed 1500 mg haem iron kg -1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
50
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 31 publications
(43 reference statements)
7
50
4
Order By: Relevance
“…The results indicated that nano-Fe and ferrous sulfate had different metabolic pathways, although both the inorganic form crossed the intestinal barrier. Thus iron bioavailability depended not only on its absorption by the intestine, but also on its conversion to a biologically active form (Andersen et al 1997). In support to the present study, the nano form of iron oxide (Fe 2 O 3 ) is highly bioavailable (96 % similarity with FeSO 4 ) in rats without tissue accumulation (Hilty et al 2010a, b nature).…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…The results indicated that nano-Fe and ferrous sulfate had different metabolic pathways, although both the inorganic form crossed the intestinal barrier. Thus iron bioavailability depended not only on its absorption by the intestine, but also on its conversion to a biologically active form (Andersen et al 1997). In support to the present study, the nano form of iron oxide (Fe 2 O 3 ) is highly bioavailable (96 % similarity with FeSO 4 ) in rats without tissue accumulation (Hilty et al 2010a, b nature).…”
Section: Discussionsupporting
confidence: 68%
“…Iron deficiency causes immune suppression, growth depression, changes in hematological parameters, susceptibility to diseases, poor food conversion and microcytic anemia in common carp (Tacon 1992;Andersen et al 1996;Kawatsu 1972;Sakamoto and Yone 1978). Iron is thus essential and in excess can be toxic (Salte et al 1994;Andersen et al 1997). Fish can absorb soluble iron from the water across the gill membrane and intestinal mucosa (Roedar and Roedar 1966;Sealey et al 1997).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in accord with previous results in Atlantic salmon (Bjørnevik and Maage 1993;Andersen et al 1996Andersen et al , 1998 and rainbow trout (Carriquiriborde et al 2004). However, my study did show that iron-1 supplement (1.51 × 10 3 mg iron/kg diet), but not iron-2 supplement (3.17 × 10 3 mg iron/kg diet), improved burst (Kawatsu 1972;Ikeda et al 1973;Sakamoto and Yone 1978;Andersen et al 1997;Carriquiriborde et al 2004), whereas an excess of supplemented iron has induced lower Hb concentrations in rainbow trout (Standal et al 1997) and Atlantic salmon . Excessive iron has been shown to lead to the oxidation of dietary lipids and/or polyunsaturated fats, adversely affecting the quality of the diet (Desjardins et al 1987).…”
Section: -4 Development Of Techniques To Improve the Seed Quality Omentioning
confidence: 96%
“…In particular, experimentally induced lack of iron may cause microcytic anaemia or low haemoglobin levels in salmonids (Kawatsu 1972;Andersen et al 1996), channel catfish (Gatlin and Wilson 1986), Japanese eel (Nose and Arai 1979), yellowtail, Seriola quinqueradiata (Ikeda et al 1973) and red sea bream. On the other hand, excessive amounts of dietary iron may not always be beneficial to farmed fish (Salte et al 1994;Andersen et al 1997) and can be connected with increased bacterial load (Fouz et al 1994).…”
Section: Introductionmentioning
confidence: 99%